PENGARUH INFLASI, INVESTASI DAN UPAH MINIMUM KOTA TERHADAP PENGANGGURAN DI KOTA BATAM - Kasmawati, Kasmawati; Banjarnahor, Haposan (LPPM Universitas Putera Batam, 2019)
Unemployment is a serious problem in almost all developing countries today, such as Indonesia, especially Batam City experiencing the same problem, namely the difficulty of controlling the increase in unemployment. The situation in Indonesia in the last few years shows that the development that has been carried out is not able to provide employment opportunities to the existing working members. This study aims to determine how the influence of inflation, investment and the city minimum wage on the unemployment rate in Batam City simultaneously and partially. This study uses seven-year time series data, namely 2012-2017 obtained from BPS Batam in the form of secondary data. The analytical method used is multiple linear regression analysis techniques. Based on the processed data, it was found that inflation, investment and city minimum wages have a simultaneous and significant influence on the unemployment rate in Batam, while the partial test results obtained that investment has a negative and significant influence on the unemployment rate in Batam city while the inflation rate and the city minimum wage has no effect on the unemployment rate in the city of Batam.